2018
DOI: 10.1186/s13195-018-0376-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of brain atrophy in Genetic Frontotemporal Dementia Initiative (GENFI) cohort revealed by visual rating scales

Abstract: BackgroundIn patients with frontotemporal dementia, it has been shown that brain atrophy occurs earliest in the anterior cingulate, insula and frontal lobes. We used visual rating scales to investigate whether identifying atrophy in these areas may be helpful in distinguishing symptomatic patients carrying different causal mutations in the microtubule-associated protein tau (MAPT), progranulin (GRN) and chromosome 9 open reading frame (C9ORF72) genes. We also analysed asymptomatic carriers to see whether it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
8
33
0
1
Order By: Relevance
“…However, patients with the p.P397S MAPT variant showed a significantly older age at disease onset and slower disease progression compared with p.P301L mutation carriers. Neuroimaging of all patients revealed bitemporal atrophy in concordance with the typical atrophy pattern described in FTLD due to MAPT mutations, but with relative preservation of other areas of the brain including frontal areas …”
Section: Discussionsupporting
confidence: 74%
“…However, patients with the p.P397S MAPT variant showed a significantly older age at disease onset and slower disease progression compared with p.P301L mutation carriers. Neuroimaging of all patients revealed bitemporal atrophy in concordance with the typical atrophy pattern described in FTLD due to MAPT mutations, but with relative preservation of other areas of the brain including frontal areas …”
Section: Discussionsupporting
confidence: 74%
“…Previous cross-sectional MRI studies demonstrated atrophy in the anteromedial temporal lobe and orbitofrontal cortex in asymptomatic MAPT mutation carriers (6,19,20), while others found no difference between asymptomatic MAPT mutation carriers and controls (6,7,33). Recently, two longitudinal studies from a cohort of asymptomatic MAPT mutation carriers have reported that hippocampal volumes decline during a 2-year follow-up, but no cortical atrophy was found in longitudinal analysis with 4 years of follow-up (21,22).…”
Section: Mapt_smrimentioning
confidence: 98%
“…In asymptomatic C9orf72 mutation carriers, cross-sectional structural MRI studies consistently found a diffuse pattern of atrophy including frontal, temporal, parietal, insular, and posterior cortical regions, as well as subcortical volumes of thalamus, hippocampus, and the cerebellum (6,22,(29)(30)(31)(32), while very few studies reported no difference between asymptomatic C9orf72 mutation carriers and healthy controls (20,68). The atrophy of subcortical regions is estimated to occur as early as 25 years before the expected symptom onset in C9orf72 mutation carriers, and later involves temporal and frontal lobes at around 20 years before the expected symptom onset, and finally involving the cerebellum at around 10 years before the expected symptom onset (19).…”
Section: C9orf72_smrimentioning
confidence: 99%
See 2 more Smart Citations